Organic zirconium phosphate modified asphalt and preparation method thereof
By secondary grafting modification of zirconium phosphate, zirconium organophosphate is obtained and added to asphalt, which solves the problem of asphalt aging under high-energy ultraviolet irradiation, and significantly improves the anti-ultraviolet aging ability and low-temperature performance of asphalt.
Patent Information
- Application Number
- CN202510077938.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-17
AI Technical Summary
Existing asphalt materials age under high-energy ultraviolet irradiation, resulting in a decrease in low-temperature crack resistance and fatigue resistance, and the road surface is prone to ruts, pits and peeling.
By secondary grafting modification of ionic organosiloxane and anionic surfactant on zirconium phosphate, zirconium organosiloxane and anionic surfactant is obtained, and it is added to the asphalt to improve the low-temperature performance and resistance to ultraviolet aging.
It significantly improves the anti-ultraviolet aging ability and low temperature performance of asphalt, extends the road life, and improves the storage stability of asphalt.
Smart Images

Figure CN119842241A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of asphalt material preparation, and in particular to an organic zirconium phosphate modified asphalt and a preparation method thereof. Background Art
[0002] Asphalt pavement is widely used due to its good flatness, short construction period and easy maintenance. However, asphalt is an organic material and is easily aged by natural environmental factors such as light, oxygen and heat. Especially under high-energy ultraviolet rays, some chemical bonds in the asphalt molecules break, making the asphalt hard and brittle, resulting in a gradual decrease in the low-temperature crack resistance and fatigue resistance of the asphalt mixture. The road surface is prone to rutting, potholes and peeling, which seriously affect driving comfort and safety.
[0003] Adding modifiers to modify asphalt is one of the effective ways to improve the asphalt's resistance to UV aging. In previous studies, adding some layered inorganic substances to asphalt can effectively improve the asphalt's resistance to UV aging, such as magnesium-aluminum-based layered double hydroxide, montmorillonite, vermiculite, etc. However, inorganic particles have poor compatibility with asphalt, resulting in serious agglomeration in asphalt, which can cause serious damage to the low-temperature performance of asphalt. It is often necessary to organically treat the inorganic particles to alleviate this negative impact. In existing studies, there are many cases in which the compatibility of inorganic particles and asphalt is improved through organic treatment, but the improvement effect is limited, and the problem of poor low-temperature performance of asphalt cannot be fundamentally solved. Therefore, how to improve the asphalt's resistance to UV aging while ensuring its low-temperature performance is a technical problem that technicians in this field need to overcome. Summary of the invention
[0004] The purpose of the present invention is to provide an organic zirconium phosphate modified asphalt and a preparation method thereof to solve the problems existing in the above-mentioned prior art.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention: an organic zirconium phosphate modified asphalt, the raw materials of which include, by weight: 100 parts of base asphalt and 5 to 15 parts of organic zirconium phosphate;
[0007] The organic zirconium phosphate is obtained by sequentially surface-modifying zirconium phosphate with an ionic organic siloxane and an anionic surfactant.
[0008] The present invention utilizes ionic organosiloxane and anionic surfactant to perform secondary grafting on the surface of zirconium phosphate, so that the surface of zirconium phosphate has a long-chain structure, thereby obtaining organic zirconium phosphate. The two graftings of ionic organosiloxane and anionic surfactant promote the transformation of zirconium phosphate from nano-scale solid powder to fluid-like material, which can effectively avoid the agglomeration phenomenon between zirconium phosphate particles and greatly improve the compatibility of zirconium phosphate with asphalt. Adding an organic zirconium phosphate modifier that tends to be fluid-like to asphalt can not only improve the low-temperature performance of asphalt (secondary surface grafting makes the organic zirconium phosphate have a flexible long-chain structure, greatly improves the hydrophobicity, and reduces the density difference with asphalt, which is beneficial to improve the compatibility of zirconium phosphate with asphalt, and improves the storage stability of modified asphalt. In addition, the flexible long-chain structure can also improve the low-temperature deformation ability and low-temperature crack resistance of asphalt), and its unique layered structure can effectively absorb and block ultraviolet rays, greatly improving the anti-ultraviolet aging ability of asphalt. The present invention effectively improves its anti-ultraviolet aging ability while ensuring the low-temperature performance of asphalt.
[0009] Furthermore, the preparation step of the organic zirconium phosphate includes: hydroxyl-modifying zirconium phosphate to obtain hydroxylated zirconium phosphate; dispersing the hydroxylated zirconium phosphate in water, then adding a methanol solution of an ionic organosiloxane, stirring for 2 to 4 hours, and then adding an aqueous solution of an anionic surfactant, heating and stirring for 10 to 12 hours to obtain the organic zirconium phosphate (that is, firstly performing a primary grafting modification on zirconium phosphate using an ionic organosiloxane to obtain a primary grafted zirconium phosphate, and then performing a secondary grafting modification on the primary grafted zirconium phosphate using an anionic surfactant to obtain a secondary grafted zirconium phosphate, namely the organic zirconium phosphate, and the grafting modification process and the grafting structure schematic diagram are as shown in Figure 1 shown).
[0010] Hydroxyl modification of zirconium phosphate can make the hydroxyl group activity on the surface of zirconium phosphate higher and improve the efficiency of surface modification; dispersing the hydroxylated zirconium phosphate in water, adding a methanol solution of ionic organosiloxane and stirring can graft the ionic organosiloxane to the surface of zirconium phosphate to achieve the organicization of zirconium phosphate; adding an aqueous solution of anionic surfactant and continuing to stir can connect the anionic surfactant with the ionic organosiloxane on the surface of zirconium phosphate, further lengthening the chain structure grafted on the surface of zirconium phosphate, greatly improving the compatibility of zirconium phosphate particles with asphalt.
[0011] Furthermore, the ionic organosiloxane is an ammonium salt organosiloxane.
[0012] Ammonium salt organosiloxane can react with the hydroxyl group on the surface of zirconium phosphate, thereby grafting on the surface of zirconium phosphate and providing cations (NH 4+ ) combined with anionic surfactants.
[0013] Furthermore, the ammonium salt-based organosiloxane is one of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, dodecyldimethyl(3-trimethoxysilylpropyl)ammonium chloride and dimethyldodecyl[3-(triethoxysilyl)propyl]ammonium chloride, preferably dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride.
[0014] The carbon chain structure of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride is long, which is most similar to the structure of asphalt molecules and has good compatibility with asphalt.
[0015] Furthermore, the anionic surfactant includes sodium alkyl sulfonate, sodium alkyl aryl sulfonate, sodium alkyl sulfate, sodium secondary alkyl sulfate or sodium lignin sulfonate, preferably sodium lignin sulfonate.
[0016] Anionic surfactants can be combined with ammonium salt organosiloxanes to further increase the carbon chain length of the zirconium phosphate surface. Among them, sodium lignin sulfonate is the preferred anionic surfactant. The sodium lignin sulfonate structure is rich in phenolic hydroxyl structures, which can capture free radicals and further improve the anti-aging properties of organic zirconium phosphate modified asphalt.
[0017] Furthermore, the usage ratio of the hydroxylated zirconium phosphate, water, the methanol solution of the ionic organosiloxane and the aqueous solution of the anionic surfactant is 1 g: 8-12 g: 8-12 g: 5-10 mL.
[0018] Furthermore, the concentration of the methanol solution of the ionic organosiloxane is 30-50 wt %; the concentration of the aqueous solution of the anionic surfactant is 10-20 wt %.
[0019] Furthermore, the hydroxyl-modification of zirconium phosphate to obtain hydroxylated zirconium phosphate includes: mixing zirconium phosphate and water, adjusting the pH of the mixed solution to 9 to 11, and stirring for 8 to 10 hours to obtain the hydroxylated zirconium phosphate.
[0020] Furthermore, the mass ratio of the zirconium phosphate to water is 1:8-12.
[0021] Furthermore, after the stirring is completed, the steps of suction filtration and washing until the filtrate is neutral and drying are also included.
[0022] Furthermore, the temperature of the heating and stirring is 60-80°C.
[0023] Furthermore, after the heating and stirring, the steps of filtering, washing and vacuum drying are also included.
[0024] The second technical solution of the present invention: The preparation method of the above-mentioned organophosphate zirconium modified asphalt comprises the following steps:
[0025] The base asphalt is preheated to 150-170° C., and then organic zirconium phosphate is added thereto, and high-speed shearing is performed at a temperature of 150-170° C. for 30-60 minutes to obtain the organic zirconium phosphate modified asphalt.
[0026] Furthermore, the rotation speed of the high-speed stirring is 4000-5000 rpm.
[0027] The third technical solution of the present invention is a method for improving the anti-ultraviolet aging ability of asphalt while ensuring the low-temperature performance of asphalt, using organic zirconium phosphate to modify the base asphalt;
[0028] The organic zirconium phosphate is obtained by sequentially surface-modifying zirconium phosphate with an ionic organic siloxane and an anionic surfactant.
[0029] The present invention discloses the following technical effects:
[0030] (1) The present invention grafts ionic organosiloxane onto the surface of zirconium phosphate through surface modification, and then combines the ionic organosiloxane with an anionic surfactant to obtain an organic zirconium phosphate. The secondary grafting makes the surface of zirconium phosphate have a long carbon chain structure. Compared with ordinary zirconium phosphate and conventional surface-modified zirconium phosphate, the organic zirconium phosphate prepared by the present invention tends to be a fluid, which can greatly enhance the affinity between zirconium phosphate and asphalt, avoid agglomeration of zirconium phosphate particles in asphalt, and greatly improve the compatibility between zirconium phosphate and asphalt.
[0031] (2) The present invention adds fluid-like organic zirconium phosphate to the base asphalt, which can improve the ductility of the asphalt and enhance the crack resistance of the road under low temperature conditions, which is beneficial to extending the life of the road surface.
[0032] (3) The present invention utilizes the multi-level chemical absorption and physical shielding effect of organic zirconium phosphate on ultraviolet rays, so that the asphalt material has excellent ultraviolet blocking effect, significantly improves the aging resistance of road asphalt, and is conducive to the long-term service of asphalt pavement. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 The diagram is a grafting modification process and grafting structure diagram of the zirconium phosphate obtained by primary grafting modification of the zirconium phosphate with an ionic organic silicone oxane and secondary grafting modification with an anionic surfactant. DETAILED DESCRIPTION
[0035] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0036] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0038] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0039] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0040] As a first aspect of the present invention, the present invention provides an organic zirconium phosphate modified asphalt, wherein the raw materials include, by weight: 100 parts of base asphalt, 5 to 15 parts of organic zirconium phosphate;
[0041] The organic zirconium phosphate is obtained by sequentially surface-modifying zirconium phosphate with an ionic organic siloxane and an anionic surfactant.
[0042] As a preferred embodiment of the present invention, the ionic organosiloxane is an ammonium salt organosiloxane.
[0043] As a preferred embodiment of the present invention, the anionic surfactant includes sodium alkyl sulfonate, sodium alkyl aryl sulfonate, sodium alkyl sulfate, sodium secondary alkyl sulfate or sodium lignin sulfonate.
[0044] As a preferred embodiment of the present invention, the ammonium salt organosiloxane is one of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, dodecyldimethyl(3-trimethoxysilylpropyl)ammonium chloride and dimethyldodecyl[3-(triethoxysilyl)propyl]ammonium chloride.
[0045] As a preferred embodiment of the present invention, the ammonium salt organic siloxane is dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride; and the anionic surfactant is sodium lignin sulfonate.
[0046] As an embodiment of the present invention, the preparation step of the organic zirconium phosphate includes: hydroxyl-modifying zirconium phosphate to obtain hydroxylated zirconium phosphate; dispersing the hydroxylated zirconium phosphate in water, then adding a methanol solution of an ionic organosiloxane, stirring for 2 to 4 hours, and then adding an aqueous solution of an anionic surfactant, heating and stirring for 10 to 12 hours to obtain the organic zirconium phosphate (that is, firstly using an ionic organosiloxane to perform a primary grafting modification on zirconium phosphate to obtain a primary grafted zirconium phosphate, and then using an anionic surfactant to perform a secondary grafting modification on the primary grafted zirconium phosphate to obtain a secondary grafted zirconium phosphate, that is, the organic zirconium phosphate, the grafting modification process and the grafting structure schematic diagram are as shown in Figure 1 shown).
[0047] As an embodiment of the present invention, the hydroxyl-modification of zirconium phosphate to obtain hydroxylated zirconium phosphate includes: mixing zirconium phosphate and water, adjusting the pH of the mixed solution to 9-11 and stirring for 8-10 hours to obtain the hydroxylated zirconium phosphate.
[0048] As a preferred embodiment of the present invention, the organic zirconium phosphate is more specifically prepared by the steps of: placing 10 parts of zirconium phosphate in a beaker, adding 80 to 120 parts of water, then adding sodium hydroxide aqueous solution dropwise (there is no requirement for the concentration of sodium hydroxide aqueous solution) until the pH value of the solution reaches 9 to 11, stirring at room temperature (speed of 1000 to 2000 rpm) for 8 to 10 hours, then filtering and washing until the filtrate is neutral, and drying to obtain hydroxylated zirconium phosphate; dispersing 10g of hydroxylated zirconium phosphate in 80 to 120g of water, then dropping 80 to 120g of methanol solution of ionic organosiloxane (concentration of 30 to 50wt%), stirring (speed of 1000 to 2000rpm) for 2 to 4h; then adding 50 to 100mL of anionic surfactant aqueous solution (concentration of 10 to 20wt%), stirring at 60 to 80°C (speed of 1000 to 2000rpm) for 10 to 12h, filtering, washing, and vacuum drying to constant weight to obtain organic zirconium phosphate.
[0049] As a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned organophosphate zirconium modified asphalt, comprising the following steps:
[0050] The base asphalt is preheated to 150-170° C., and then organic zirconium phosphate is added thereto. The asphalt is sheared at a high speed (4000-5000 rpm) for 30-60 minutes at a temperature of 150-170° C. to obtain the organic zirconium phosphate modified asphalt.
[0051] As a third aspect of the present invention, the present invention provides a method for improving the anti-ultraviolet aging ability of asphalt while ensuring the low-temperature performance of asphalt, using organic zirconium phosphate to modify the base asphalt;
[0052] The organic zirconium phosphate is obtained by sequentially surface-modifying zirconium phosphate with an ionic organic siloxane and an anionic surfactant.
[0053] The organophosphate zirconium modified asphalt and the preparation method thereof of the present invention are further described below in conjunction with specific examples.
[0054] The room temperature involved in the specific implementation manner of the present invention specifically refers to 20-30°C.
[0055] The raw materials used in the specific implementation of the present invention are all common commercial products, among which the CAS number of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride is 27668-52-6, the CAS number of dodecyldimethyl(3-trimethoxysilylpropyl)ammonium chloride is 27668-53-7, the CAS number of sodium lignin sulfonate is 8061-51-6, the CAS number of sodium dodecyl sulfate is 151-21-3, and the CAS number of sodium 2,5-dimethylbenzenesulfonate is 827-19-0. The base asphalt is specifically a road base asphalt, model 70#.
[0056] Example 1
[0057] An organic zirconium phosphate modified asphalt comprises, by weight, 10 parts of organic zirconium phosphate and 100 parts of base asphalt.
[0058] The preparation method of organophosphate zirconium modified asphalt comprises the following steps:
[0059] S1. Preparation of organic zirconium phosphate: weigh 10 parts of zirconium phosphate and place them in a beaker, add 100 parts of deionized water, then add sodium hydroxide aqueous solution dropwise until the solution pH reaches 10, stir at room temperature (speed is 1500 rpm) for 10 hours, then filter and wash until the filtrate is neutral, and dry to obtain hydroxylated zirconium phosphate; take 10g of hydroxylated zirconium phosphate and disperse it in 100g of deionized water, then add 100g of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride methanol solution (40wt%) dropwise, and stir (speed is 1500rpm) for 3h; then add 75mL of sodium lignin sulfonate aqueous solution (concentration is 15wt%), stir at 70℃ (speed is 1500rpm) for 12h, filter, wash, and vacuum dry to constant weight to obtain organic zirconium phosphate;
[0060] S2. Preparation of organo-zirconium phosphate modified asphalt: preheat the base asphalt to 160°C, add organo-zirconium phosphate in proportion, and shear at high speed (rotation speed of 4000 rpm) at 160°C for 30 minutes to obtain organo-zirconium phosphate modified asphalt.
[0061] Example 2
[0062] The same as Example 1, except that the aqueous solution of sodium lignin sulfonate is replaced by an aqueous solution of sodium dodecyl sulfate of equal concentration and volume.
[0063] Example 3
[0064] The same as Example 1, except that the concentration of the methanol solution of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride added dropwise is 30 wt %.
[0065] Example 4
[0066] The same as Example 1, except that the concentration of the methanol solution of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride added dropwise is 50 wt %.
[0067] Example 5
[0068] The same as Example 1, except that the number of organic zirconium phosphate in the organic zirconium phosphate modified asphalt component is 5.
[0069] Example 6
[0070] The same as Example 1, except that the proportion of organic zirconium phosphate in the organic zirconium phosphate modified asphalt component is 15.
[0071] Example 7
[0072] The same as Example 1, except that the aqueous solution of sodium lignin sulfonate is replaced by an aqueous solution of sodium 2,5-dimethylbenzenesulfonate of equal concentration and volume.
[0073] Example 8
[0074] The same as Example 1, except that the methanol solution of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride is replaced by a methanol solution of dodecyldimethyl(3-trimethoxysilylpropyl)ammonium chloride of equal concentration and mass.
[0075] Comparative Example 1
[0076] A zirconium phosphate modified asphalt comprises, by weight, 10 parts of zirconium phosphate and 100 parts of base asphalt.
[0077] The preparation method of zirconium phosphate modified asphalt comprises the following steps:
[0078] After preheating the base asphalt to 160°C, zirconium phosphate was added in proportion and sheared at a high speed (rotation speed of 4000 rpm) at 160°C for 30 minutes to obtain zirconium phosphate modified asphalt.
[0079] Comparative Example 2
[0080] The same as Example 1, except that the concentration of the methanol solution of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride added dropwise is 20 wt %.
[0081] Comparative Example 3
[0082] The same as Example 1, except that the concentration of the methanol solution of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride added dropwise is 60 wt %.
[0083] Comparative Example 4
[0084] The same as Example 1, except that the number of organic zirconium phosphate in the organic zirconium phosphate asphalt component is 3.
[0085] Comparative Example 5
[0086] Same as Example 1, except that the number of organic zirconium phosphate in the organic zirconium phosphate modified asphalt component is 18.
[0087] Comparative Example 6
[0088] An organic zirconium phosphate modified asphalt comprises, by weight, 10 parts of organic zirconium phosphate and 100 parts of base asphalt.
[0089] The preparation method of organophosphate zirconium modified asphalt comprises the following steps:
[0090] S1. Preparation of organic zirconium phosphate: weigh 10 parts of zirconium phosphate and place them in a beaker, add 100 parts of deionized water, then add sodium hydroxide aqueous solution dropwise until the pH value of the solution reaches 10, stir at room temperature (speed is 1500 rpm) for 10 hours, filter and wash until the filtrate is neutral, and dry to obtain hydroxylated zirconium phosphate; take 10g of hydroxylated zirconium phosphate and disperse it in 100g of deionized water, then add 100g of methanol solution (40wt%) of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride dropwise, stir (speed is 1500 rpm) for 3 hours, then filter, wash, and vacuum dry to constant weight to obtain organic zirconium phosphate;
[0091] S2. Preparation of organo-zirconium phosphate modified asphalt: preheat the base asphalt to 160°C, add organo-zirconium phosphate in proportion, and shear at high speed (rotation speed of 4000 rpm) at 160°C for 30 minutes to obtain organo-zirconium phosphate modified asphalt.
[0092] Comparative Example 7
[0093] An organic zirconium phosphate modified asphalt comprises, by weight, 10 parts of organic zirconium phosphate and 100 parts of base asphalt.
[0094] The preparation method of organophosphate zirconium modified asphalt comprises the following steps:
[0095] S1. Disperse 10 g of zirconium phosphate in 100 g of deionized water, then dropwise add 100 g of a methanol solution (40 wt%) of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, and stir (at a speed of 1500 rpm) for 3 h; then add 75 mL of an aqueous solution (at a concentration of 15 wt%) of sodium lignin sulfonate, stir at 70° C. (at a speed of 1500 rpm) for 12 h, filter, wash, and vacuum dry to constant weight to obtain an organic zirconium phosphate;
[0096] S2. Preparation of organo-zirconium phosphate modified asphalt: preheat the base asphalt to 160°C, add organo-zirconium phosphate in proportion, and shear at high speed (rotation speed of 4000 rpm) at 160°C for 30 minutes to obtain organo-zirconium phosphate modified asphalt.
[0097] Test Example 1
[0098] In order to verify the relevant performance of modified asphalt, the modified asphalt prepared by 70# base asphalt, Examples 1-8 and Comparative Examples 1-7 were tested for ductility according to the national standard GBT4508-2010 (test temperature is 5°C) to evaluate the low-temperature performance of asphalt. The greater the ductility of asphalt, the better the ductility, which proves that the low-temperature performance of asphalt is better. In addition, the asphalt samples were subjected to UV aging test (UV light intensity 800w / m 2, temperature is 60℃, aging time is 3 days), and a dynamic shear rheometer is used to perform temperature scanning experiments on the samples before and after aging, and the complex modulus aging index (CAI) is calculated to evaluate the anti-aging ability of asphalt. The smaller the value of the complex modulus aging index, the stronger the anti-aging ability of asphalt. The aging index calculation formula is as follows:
[0099]
[0100] Where: aging represents the index after aging, and origin represents the index before aging.
[0101] The performance test results are shown in Table 1:
[0102] Table 1
[0103]
[0104]
[0105] According to the experimental data recorded in Table 1, by comparing 70# base asphalt, Example 1 and Comparative Example 1, it can be obtained that zirconium phosphate can improve the anti-ultraviolet aging ability of asphalt, but will damage the ductility of asphalt under low temperature conditions, that is, the addition of zirconium phosphate will affect the low temperature performance of asphalt; the organic zirconium phosphate obtained by secondary grafting surface modification can improve the low temperature performance and anti-ultraviolet aging ability of asphalt, and the organic zirconium phosphate modified asphalt has better anti-ultraviolet aging performance than the zirconium phosphate (without organic treatment) modified asphalt. This is attributed to the fact that organic treatment solves the agglomeration problem of zirconium phosphate particles, greatly improves the dispersibility of zirconium phosphate in asphalt, and improves the compatibility of organic zirconium phosphate and asphalt. In addition, the uniform dispersion of the layered structure is beneficial to improve its effect of absorbing and shielding ultraviolet radiation.
[0106] By comparing Examples 1, 3, and 4 with Comparative Examples 2 and 3, it can be obtained that, during the surface modification process of zirconium phosphate, if the concentration of the methanol solution of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride is too low, the surface modification of the zirconium phosphate is insufficient, which affects the organic effect of the zirconium phosphate and causes the organic zirconium phosphate to have no obvious improvement on the low-temperature performance and anti-ultraviolet aging performance of asphalt; if the concentration of the methanol solution of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride is too high, the improvement on the performance of asphalt is limited. Considering the preparation cost, its concentration should not be too high.
[0107] By comparing Examples 1, 5, and 6 with Comparative Examples 4 and 5, it can be seen that in the preparation process of organophosphate zirconium modified asphalt, if the dosage of organophosphate zirconium is too low, the effect of improving the low temperature performance and anti-ultraviolet aging performance of asphalt is poor. If the dosage of organophosphate zirconium is too high, the improvement of the low performance of asphalt is limited. Considering the preparation cost, its dosage should not be too high.
[0108] By comparing Example 1, Example 2 and Example 7, it can be found that using sodium lignin sulfonate rich in phenolic hydroxyl structure as an anionic surfactant is more conducive to improving the anti-aging properties of organic zirconium phosphate modified asphalt, while using sodium dodecyl sulfate with a long chain structure as an anionic surfactant can more significantly improve the low-temperature performance of organic zirconium phosphate modified asphalt.
[0109] By comparing Example 1 and Example 8, it can be obtained that when the ammonium salt organosiloxane is dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, a better organic effect can be achieved, and the improvement of the low temperature performance and anti-ultraviolet aging performance of asphalt is more obvious.
[0110] By comparing Example 1 with Comparative Example 6, it can be found that secondary grafting on the surface of zirconium phosphate is beneficial to further improve the low-temperature performance and anti-aging performance of organic zirconium phosphate modified asphalt.
[0111] By comparing Example 1 with Comparative Example 7, it can be found that hydroxylation of zirconium phosphate is beneficial to improving the organic effect of zirconium phosphate, thereby increasing the low temperature performance and anti-aging performance of asphalt.
[0112] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. An organophosphate zirconium modified asphalt, characterized in that: The raw materials include, by weight: 100 parts of base asphalt, 5 to 15 parts of organic zirconium phosphate; The organic zirconium phosphate is obtained by sequentially surface-modifying zirconium phosphate with an ionic organic siloxane and an anionic surfactant.
2. The organophosphate zirconium modified asphalt according to claim 1, characterized in that The ionic organosiloxane is an ammonium salt organosiloxane; the anionic surfactant includes sodium alkyl sulfonate, sodium alkyl aryl sulfonate, sodium alkyl sulfate, sodium secondary alkyl sulfate or sodium lignin sulfonate.
3. The organophosphate zirconium modified asphalt according to claim 2, characterized in that The ammonium salt organic siloxane is one of dimethyl octadecyl [3- (trimethoxysilyl) propyl] ammonium chloride, dodecyl dimethyl (3-trimethoxysilyl propyl) ammonium chloride and dimethyl dodecyl [3- (triethoxysilyl) propyl] ammonium chloride.
4. The organophosphate zirconium modified asphalt according to claim 1, characterized in that The preparation steps of the organic zirconium phosphate include: performing hydroxyl modification on zirconium phosphate to obtain hydroxylated zirconium phosphate; dispersing the hydroxylated zirconium phosphate in water, then adding a methanol solution of an ionic organosiloxane, stirring for 2 to 4 hours, then adding an aqueous solution of an anionic surfactant, heating and stirring for 10 to 12 hours, to obtain the organic zirconium phosphate.
5. The organophosphate zirconium modified asphalt according to claim 4, characterized in that The dosage ratio of the hydroxylated zirconium phosphate, water, the methanol solution of the ionic organosiloxane and the aqueous solution of the anionic surfactant is 1g:8-12g:8-12g:5-10mL.
6. The organophosphate zirconium modified asphalt according to claim 4, characterized in that The concentration of the methanol solution of the ionic organosiloxane is 30-50 wt %; the concentration of the aqueous solution of the anionic surfactant is 10-20 wt %.
7. The organophosphate zirconium modified asphalt according to claim 4, characterized in that: The hydroxyl-modification of zirconium phosphate to obtain hydroxylated zirconium phosphate includes: mixing zirconium phosphate and water, adjusting the pH of the mixed solution to 9 to 11, and stirring for 8 to 10 hours to obtain the hydroxylated zirconium phosphate.
8. The organophosphate zirconium modified asphalt according to claim 4, characterized in that The temperature of the heating and stirring is 60-80°C.
9. The method for preparing the organophosphate zirconium modified asphalt according to any one of claims 1 to 8, characterized in that: The following steps are involved: The base asphalt is preheated to 150-170° C., and then organic zirconium phosphate is added thereto, and high-speed shearing is performed at a temperature of 150-170° C. for 30-60 minutes to obtain the organic zirconium phosphate modified asphalt.
10. A method for improving the anti-ultraviolet aging ability of asphalt while ensuring the low temperature performance of asphalt, characterized in that: Modification of base asphalt using zirconium organophosphate; The organic zirconium phosphate is obtained by sequentially surface-modifying zirconium phosphate with an ionic organic siloxane and an anionic surfactant.
Citation Information
Patent Citations
Lignin grafted magnesium aluminum-based layered double hydroxide modifier, anti-ultraviolet ageing asphalt and preparation method thereof
CN106700579A
Sodium lignosulfonate grafted magnesium-aluminum-based LDH (layered double hydroxide) modifier, ultraviolet-aging-resistant SBR (styrene-butadiene rubber) modified asphalt and preparation method of ultraviolet-aging-resistant SBR modified asphalt
CN106832973A
Modifier for functionally-assembled magnesium-aluminum-based layered dihydroxy metal hydroxide (LDHs), and preparation method and application thereof
CN110819129A
Organic zirconium phosphate modifier based on waste plastic derivative, anti-aging asphalt-based material and preparation method thereof
CN119101287A
Anti-aging polyurethane-zirconium phosphate composite modified asphalt and preparation method thereof
CN119101367A